2016
DOI: 10.1111/jgh.13233
|View full text |Cite
|
Sign up to set email alerts
|

Rapid metabolizer genotype of CYP2C19 is a risk factor of being refractory to proton pump inhibitor therapy for reflux esophagitis

Abstract: The present meta-analysis demonstrates that CYP2C19 RMs with RE have an increased risk of being refractory to PPI therapy compared with PMs. Individualized dosing regimen with PPIs based on CYP2C19 genotype might be a valid therapeutic strategy for overcoming insufficient gastric acid inhibition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
40
0
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(57 citation statements)
references
References 58 publications
1
40
0
16
Order By: Relevance
“…Collectively, the data support better outcomes in management of GERD and higher success rate of H. pylori eradication in IM and PM phenotypes compared to NM, RM, and UM phenotypes (Table 4) [59,60,6264], which is consistent with the higher intragastric pH achieved in patients with reduced CYP2C19 activity and higher PPI concentrations [7779]. While many studies suggest this to be true regardless of the PPI used, some reports have suggested that the therapeutic outcomes are less influenced by genotype in PPIs with less dependence on CYP2C19 metabolism, namely rabeprazole and esomeprazole [71,73,80].…”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 70%
See 1 more Smart Citation
“…Collectively, the data support better outcomes in management of GERD and higher success rate of H. pylori eradication in IM and PM phenotypes compared to NM, RM, and UM phenotypes (Table 4) [59,60,6264], which is consistent with the higher intragastric pH achieved in patients with reduced CYP2C19 activity and higher PPI concentrations [7779]. While many studies suggest this to be true regardless of the PPI used, some reports have suggested that the therapeutic outcomes are less influenced by genotype in PPIs with less dependence on CYP2C19 metabolism, namely rabeprazole and esomeprazole [71,73,80].…”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 70%
“…Convincing evidence for the effect of CYP2C19 on the clinical outcomes of GERD treatment comes from a recent meta-analysis by Ichikawa et al highlighting the risk of therapeutic failure associated with the NM phenotype [64]. In this analysis, the effect of genotype status was evaluated using combined analysis of 19 published studies, which included patients with GERD.…”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 99%
“…In the present study, patients who were EMs and negative for H. pylori infection had a median gastric pH >4 HTR of 26.5% while consuming PPIs, which is similar to that of Miki's report. Furthermore, in a meta-analysis of only patients with RE, EMs were found to be at a higher risk of being refractory to PPI therapy than were PMs (OR 1.661, 95% CI 1.023-2.659, p = 0.040) [20]. Therefore, patients with RE who are CYP2C19 EMs without H. pylori infection are considered to have a high risk of being refractory to standard dose PPI therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are no data available on the effect of vonoprazan on the volume of gastric contents, PPI therapy has previously been shown to decrease gastric volume significantly and reflux events during post-prandial periods [30,31]. Several studies have proved that vonoprazan is more potent than PPIs in inhibiting the secretion of gastric acid [20,23]; therefore, it would be expected that vonoprazan can reduce the volume of gastric contents more than PPIs can, resulting in reduction of reflux volume and proximal reflux events during vonoprazan therapy. However, the effect of the size and composition of a meal should also be considered.…”
Section: Discussionmentioning
confidence: 99%
“…Фенотип «быстрых» метаболизаторов является значимым фактором риска рефрактерности к тера-пии ИПП у лиц с ГЭРБ (ОШ 1,661, 95% ДИ: 1,023-2,659, p = 0,040) [51]. Помимо этого, менее выражен-ный антисекреторный эффект у «быст рых» метабо-лизаторов определяет низкую эффек тивность эра-дикационной терапии инфекции Helicobacter pylori (H. pylori) у лиц этого фенотипа [50,52].…”
Section: таблица 1 эволюция лечения кислотозависимых заболеванийunclassified